Leveraging spatial econometrics for enhanced impact assessment: Insights from agricultural innovation - Song, Chun; Urbani, Ilaria (2024)
This learning note explores spatial econometrics as a key tool in impact assessment for agricultural innovation. By accounting for geographic, social, and economic proximities, spatial econometrics enhances causal analysis and tailors interventions across diverse locations. Used at the Alliance with biophysical and socio-economic models, it supports geo-targeting and scaling of agricultural innovations, enabling more reliable, location-sensitive assessments. Part of the MELIAF series, this note underscores spatial econometrics’ role in refining impact evaluations.